2020
DOI: 10.1101/2020.09.22.308809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coherent theta activity in the medial and orbital frontal cortices encodes reward value

Abstract: This study examined how the medial frontal (MFC) and orbital frontal (OFC) cortices process reward information to guide behavior. We simultaneously recorded local field potentials in the two areas as rats consumed liquid sucrose rewards and examined how the areas collectively process reward information. Both areas exhibited a 4-8 Hz "theta" rhythm that was phase locked to the lick cycle. The rhythm similarly tracked shifts in sucrose concentrations and fluid volumes, suggesting that it is sensitive to general … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
2
4
0
Order By: Relevance
“…Our results confirm and extend a recent report that ACC-OFC theta coherence encodes reward value (Amarante and Laubach, 2021), since the ACC-OFC interaction we observed occurred during initial learning of both S-O and A-O tasks, but not during reversal learning. A noteworthy difference from Amarante & Laubach (2021) is that this group studied coherence during reward consumption (i.e., licks).…”
Section: Ofc Theta Alone Signals Accuracy During Reversal Learning S-o Reversal Learningsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirm and extend a recent report that ACC-OFC theta coherence encodes reward value (Amarante and Laubach, 2021), since the ACC-OFC interaction we observed occurred during initial learning of both S-O and A-O tasks, but not during reversal learning. A noteworthy difference from Amarante & Laubach (2021) is that this group studied coherence during reward consumption (i.e., licks).…”
Section: Ofc Theta Alone Signals Accuracy During Reversal Learning S-o Reversal Learningsupporting
confidence: 92%
“…Our results confirm and extend a recent report that ACC-OFC theta coherence encodes reward value (Amarante and Laubach, 2021), since the ACC-OFC interaction we observed occurred during initial learning of both S-O and A-O tasks, but not during reversal learning. A noteworthy difference from Amarante & Laubach (2021) is that this group studied coherence during reward consumption (i.e., licks). We note that the increase in theta power we report here occurred immediately following a correct choice but preceded most reward collection times (1.5-2.5 sec) and consumption of the sucrose pellet.…”
Section: Ofc Theta Alone Signals Accuracy During Reversal Learning S-o Reversal Learningsupporting
confidence: 92%
See 1 more Smart Citation
“…Activity in vmOFC is not consistent with a signaling of the subjective value of a received reward in these experiments (Amarante and Laubach, 2020; Padoa-Schioppa and Assad, 2006). This is because the subjective value of the same received reward should be equal regardless of whether the reward was predicted, and further the subjective value of the receipt of a predicted reward should be larger than the subjective value of the omission of a predicted reward.…”
Section: Supplementary Informationmentioning
confidence: 57%
“…It has previously been observed that orbitofrontal cortical neurons represent the relative value of a reward in comparison to other available options (Tremblay and Schultz, 1999) (though see (Amarante and Laubach, 2020; Padoa-Schioppa and Assad, 2008)). Such a relative value signal has also been clearly demonstrated in other brain regions (Louie et al, 2011; Ottenheimer et al, 2018).…”
Section: Supplementary Informationmentioning
confidence: 99%